Efforts of Dormitory Supervisors in Overcoming Problems in the Quran Memorization Dormitory - Azimah Khaira Ummah; Nur Asikin Kakoh; Muhammad Barry Mahmudi; Alfina Zulyan Wardani; Azizah Khaira Ummah (Journal of Theory and Research Memorization Quran, 2025)
The dormitory is a temporary residence for students or students who are away from home while studying. The diversity found in dormitories in the form of habits, culture, religion, mindset and way of life is a challenge for dormitory coaches. Dormitory coaches have their own share in dealing with conflicts that occur in the dormitory. Therefore, this study aims to explore the efforts of dormitory coaches in overcoming various problems faced by dormitory residents, including religious, educational, health, hygiene, and social aspects. This research uses a qualitative method with a case study approach. Data sources were taken from ten informants consisting of dormitory coaches, students, and dormitory administrators, data sources were taken through in-depth interviews. The results of this study indicate that there are six efforts of dormitory coaches in overcoming problems that occur in the dormitory which include i) forming religious programs ii) guiding and facilitating the learning process at night iii) prohibition of certain types of food and drinks iv) provision of health services v) making a daily picket schedule vi) implementing the ukhuwah program.